The Influence Of Tax Understanding And Tax Awareness On Taxpayer Compliance In Paying Land And Building Tax (PBB) In Muara Payang Village, Seginim District, South Bengkulu Regency - Putri, Tiara Renita; Susena, Karona Cahya; Subhi, Ramadan (Universitas Dehasen Bengkulu, 2025)
The background of this research is the low level of taxpayer compliance in Muara Payang Village in fulfilling their obligation to pay Land and Building Tax (PBB). The purpose of this study is to examine whether tax understanding and tax awareness have an influence on taxpayer compliance in paying Land and Building Tax (PBB) in Muara Payang Village, Seginim District, South Bengkulu Regency. This type of research is quantitative. The data collection method in this study was carried out by distributing questionnaires through Google Form. The sampling technique used was the Slovin formula, resulting in a sample of 150 taxpayers in Muara Payang Village, Seginim District, South Bengkulu Regency. The data were then processed using SPSS version 26. The results of the study show that Tax Understanding has a positive and significant effect on Taxpayer Compliance, as evidenced by a t-value of 8.613 > t-table 1.976 and a significance value of 0.000 < 0.05. Therefore, H₀ is rejected and Hₐ is accepted, meaning H₁ is accepted. Tax Awareness also has a positive and significant effect on Taxpayer Compliance, with a t-value of 3.141 > t-table 1.976 and a significance value of 0.002 < 0.05. Therefore, H₀ is rejected and Hₐ is accepted, meaning H₂ is accepted. Tax Understanding and Tax Awareness simultaneously have a significant effect on Taxpayer Compliance, as indicated by the F-test result where the F-value is 54.925, greater than the F-table value of 3.06, and the significance value is 0.000 < 0.05.